Development of e-module using context of the Muara Enim traditional house on polyhedron materials - Harisman Nizar; Emy Ismayanti; Agustiany Dumeva Putri (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
: This study aims to produce e-module teaching materials based on PMRI on polyhedron material for class VIII SMP using the context of the Muara Enim traditional house using the Canva application, as well as to find out whether this e-module is valid, practical, and has a potential effect on problem-solving abilities in students. Learners. The research method used is R&D using Tessmer. The research process consists of two stages: the first preliminary stage, which includes the preparation and design stages, and the second assessment, which is a formative flow that provides for self-evaluation, expert review, one-to-one, small groups, and field tests. Compiled with the PMRI approach and linked to the context of the Muara Enim traditional house, the stages of testing the presentation of e-module teaching materials. The e-module learning materials were given to class VIII students of Junior High School. At this time, it shows that using e-modules in making teaching materials is valid and practical with qualitative analysis. The validity of teaching materials is carried out at the expert review stage using the validator's comments and suggestions—validity aspects in terms of the E-module's content, construction, and language. Practicality is done in the one-to-one, small group, and field test stages by looking at student comments and suggestions. The potential effect is the result of student evaluation tests used in field tests. The developed e-module teaching materials have a possible effect with an accuracy rate of 72.6%, so the e-module is potentially impacting mathematical problems. The researcher suggests that future researchers make the questions in the e-module more varied. Questions vary by providing questions from cognitive levels from C1 to C6.